Should we use large scale healthcare interventions without clear evidence that benefits outweigh costs and harms? Yes. Issue 7656 (5th June 2008) - Crump, Bernard
Abstract : Obtaining definitive evidence on the effects of large scale interventions can be difficult. Bernard Crump believes that implementation with careful monitoring is justified but Seth Landefeld and colleagues ( doi: 10.1136/bmj.a144 ) argue that acting without proof of net benefit is both costly and potentially damaging to health